The Transformation of Islamic Education in Indonesia: An Analysis of Modernization and Reform Efforts - Mar’atus Sholihah; Nanda Rivat Cahya Dinullah; Septiana Purwaningrum; Muawanah Muawanah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The modernization and reform of Islamic education in Indonesia are essential responses to globalization, scientific and technological advancement, and moral decline while maintaining the foundational values of Islam. This study aims to analyze the processes, forms, and challenges of modernization and reform in Islamic education in Indonesia, with particular attention to curriculum development, learning methods, and educational institutions. This study employed a qualitative library research approach. Primary data were drawn from Zubairi’s (2018) Modernisasi Pendidikan Islam / Modernization of Islamic Religious Education, while secondary data were obtained from relevant scholarly journal articles indexed in Google Scholar. The findings indicate that modernization in Islamic education has been implemented through the integration of religious and general knowledge, the use of digital technology, participatory and contextual learning approaches, and professional educational management. Educational reform has also developed dynamically in response to changes in Indonesia’s national context, from the post-independence period to the Reform Era, with the aim of improving educational quality. However, the transformation of Islamic education continues to face several challenges, including the persistence of the knowledge dichotomy, limited educational facilities and infrastructure, disparities in teacher quality, and moral decline. This study concludes that strong collaboration among the government, educational institutions, and society is necessary to develop an integrative and adaptive Islamic education system. Theoretically, this study contributes to the literature on Islamic educational modernization by clarifying the relationship between reform, knowledge integration, and institutional adaptation. Practically, it offers implications for strengthening Islamic educational institutions in producing Muslim generations who are intellectually competent, spiritually grounded, and socially responsible.